A systematic review on the accuracy of manufacturing techniques for cobalt chromium fixed dental prostheses. Issue 1 (1st January 2020) - Svanborg, Per; Hjalmarsson, Lars
Abstract: Purpose: To compare the fit and assess the accuracy of tooth-supported single and multi-unit FDPs in cobalt chromium fabricated using different manufacturing techniques. Materials and methods: A systematic search was performed in three databases; PubMed, Scopus, and Web of Science, using clearly specified search terms and inclusion criteria. The search yielded 1071 articles and included 18 articles in the analysis. Data regarding the fit analyses and the methods of manufacturing were extracted and the accuracy was defined as the fit result minus the pre-set cement spacer. Internal gap (IntG) was the mean of all the internal measuring points and total gap (TotG) was the mean of all measuring points (marginal, cervical, chamfer, axial, occlusal). Results: The total gap results for fit and accuracy irrespective of manufacturing technique were 96 μm and 54 μm for single crowns, 107 μm and 54 μm for multi-unit FDPs, and 98 μm and 54 μm for both single crowns and multi-unit FDPs combined. For total gap of single crowns soft milling had the highest accuracy, for multi-unit FDPs additive manufactured restorations had the highest accuracy. With the results grouped by impression technique, the accuracy for total gap was highest for digital impressions and lower for conventional impressions. Conclusions: Due to the inherent limitations of this systematic review, it still remains unclear what effect the manufacturing technique has on the fit of FDPs. However, the descriptive results suggest that the marginal fit of cobalt chromium FDPs is not negatively affected by the manufacturing technique.